Особливості вербалізації сегмента “фантастичні істоти” концепту ФАНТАЗІЯ в американському віршованому дискурсі для дітей - Наконечна, Ю. С.; Nakonechna, Y. S. (Східноєвропейський національний університет ім. Лесі Українки, 2011)
Статтю присвячено особливостям вербалізації сегмента “фантастичні істоти” концепту ФАНТАЗІЯ в аме- риканському віршованому дискурсі для дітей. У дослідженні виокремлено структурні елементи сегмента “фантастичні істоти”, які представлені вісьмома групами та відповідними їм підгрупами номінацій персонажів. This article is devoted to the verbalization of the segment “fantastic creatures” of the concept of FANTASY in American versified discourse for children. In the course of research, the structural elements of the segment “fantastic creatures” have been identified. These elements are verbalized by eight groups and the corresponding subgroups of the nominations of characters in the above mentioned discourse.
The Verbalization of the Segment “Fantastic Creatures” of the Concept of FANTASY in American Versified Discourse for Children
Keywords: концепт ФАНТАЗІЯ; сегмент “фантастичні істоти”; американський віршований дискурс для дітей; concept of FANTASY; segment “fantastic creatures”; American versified discourse for children